Patients' perceptions and experiences of venous leg ulceration and their attitudes to larval therapy: an in‐depth qualitative study. (15th February 2013) - McCaughan, Dorothy; Cullum, Nicky; Dumville, Joanne
Abstract: Background: Venous leg ulcers are a common and distressing condition that can impair quality of life. Larval therapy has been widely promoted for the treatment of different types of chronic wounds, yet little is known about its acceptability to patients. Objectives: To explore patients' experiences of venous leg ulceration and of the acceptability of larval therapy as a treatment. Design: Qualitative study, using semi‐structured interviews alongside a randomized controlled trial. Interview data were transcribed and analysed for thematic content. Data were collected from April 2007 to July 2007. Setting and participants: Eighteen people (12 men, 6 women), aged between 29 and 93 years (median age 64 years), with at least one venous leg ulcer, took part in the study. Fourteen people were recruited from two vascular clinics (one attached to a hospital and the other located in a community setting). A further four people were recruited through referral from a team of community nurses. Findings: Participants portrayed lives blighted by the presence of one or more leg ulcers. The majority were willing to try 'maggots' (larvae) and able to overcome feelings of squeamishness because of their strong desire to heal their ulcers. Five people treated with larvae were included in the study. Initial improvements in the condition of their ulcers were not sustained, and two participants experienced severe pain. Discussion and conclusions: Patients may hold unrealistic expectations that larval therapy will effect a longed‐for cure for their leg ulcer(s) but an absence of healing may lead to feelings of disappointment or despair.